Effect of Partial Replacement of Cement with Waste Marble Powder in Cement Pastes - Vardhan, Kirti (My University, 2015)
The economical benefit of using waste material usually attributes to the reduction of the amount of expensive and or scarce ingredients with cheap materials. Environmentally, when industrial wastes are recycled, so that not only the CO2 emissions are reduced but residual products from other industries are reused and therefore less material is dumped as landfill and more natural resources are saved. The waste materials which have potential to be used as an alternative to cement are waste marble powder, coal fly ash, diatomite etc. Waste marble powder has been taken for detailed study as a lot of research work has already been done on other waste materials and there is a lot of scope for research on WMP as a replacement to cement, sand or both. Here in this case, cement has been partially replaced with in varying proportions from 0% to 50% and its effect was analysed on the standard consistency, soundness, setting times of cement and compressive strength of cement mortar mixes. The study shows that the Standard consistency of cement paste made with cement partially replaced with WMD has slightly decreased due to lesser specific surface of WMD as compared to cement is less than the specific surface of cement. Soundness of cement is not affected by use of WMP. The initial and final setting times remain well within the permissible limits as per codal provisions. Compressive strength of cement mortar decreases by 10% with 10% replacement of cement with WMP. Hence use of waste marble powder upto 10% as a cement replacement is recommended as per strength requirements so as to utilize waste marble powder, which is an humanitarian issue, requiring urgent attention to safeguard against environmental pollution.
M.E. (Structural Engineering)
Keywords: marble dust; cement paste; CED